Medical Risk Assessment, Medical Errors, And Legal Accountability - Arimbi, Diah (Jurisprudentie : Jurusan Ilmu Hukum Fakultas Syariah dan Hukum, 2025)
Healthcare services are inherently complex and challenging activities, particularly in terms of medical risks and the potential for medical errors or malpractice. Medical risks, medical errors, and malpractice in healthcare are interconnected concepts that are interesting to examine together, as all three can have negative consequences for the patient’s body. Therefore, it is essential to explore them further to distinguish between them clearly. This research aims to examine the legal aspects of the relationship between medical risk, medical error, and malpractice, as well as the potential legal liabilities that may arise in medical practice. The approach used is normative juridical, with primary sources including legislation, legal principles, and relevant scholarly literature. The findings suggest that medical risks are inherent consequences of any medical action, which cannot always be avoided, and do not imply negligence if performed in accordance with professional standards, ethics, and operational procedures. In contrast, medical errors refer to unintentional mistakes in the implementation or planning of medical actions, which still need to be evaluated to prevent recurring adverse impacts. Medical malpractice occurs when there is an element of negligence and a violation of professional standards that results in harm to the patient, potentially leading to both criminal and civil legal liability. By clearly distinguishing between medical risk, medical error, and malpractice, this research highlights the importance of therapeutic communication, the application of informed consent principles, and the need for balanced legal protection that balances both patient safety and medical personnel protection. Keywords: Medical risk, Medical error, Malpractice, Legal liability, Healthcare services.